Distribution of species of dipterocarpaceae and moraceae families in primary and secondary forests - Anis Amalina, Adam. (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study aimed to investigate the distribution of Dipterocarpaceae and Moraceae in terms of genus and species diversity in primary and secondary forests. To accomplish the objective of the study, 10 plots of 20 m x 20 m were randomly established in each forest type. Tree species of Dipterocarpaceae and Moraceae were identified, counted, and the height and DBH of trees 5 cm were recorded. Density and basal area per hectare were computated for data analysis. A total of 338 stems/ha of dipterocarp trees were recorded in primary forest at Mount Matang with a total basal area of 4.2144 m2 /ha and 5 stems/ha of dipterocarp in secondary forest in Bau with a total basal area of 0.0403m2 /ha. As for tree species of Moraceae, 42 stems/ha,with a total basal area of 0.5457 m2 /ha and 122 stems/ha with the total basal area of 4.8108 m2 /ha were recorded in primary and secondary forests respectively. The result obtained shows dipterocarps are more abundantly distributed in Mount Matang compared to Bau secondary forest and six out of 16 genera of the family were recorded. The study concludes that forest structure is the main factor in the difference of tree distribution. Tree species of Moraceae are found to be distributed in both forest types. Unlike Dipterocarpaceae, only Artocarpus and Ficus were recorded for Moraceae and Artocarpus constitutes the highest tree count. Occurrence of Moraceae in both forest is related to their importance in food chain of the ecosystem in which the trees produce fruits consumed by wildlife such as primates, bats and frugivorous birds.